Tactics of Antiarrhythmic Therapy in Comorbid Elderly and Senile Patients with Paroxysmal and Recurrent Atrial Fibrillation - M. H. Fedorova; V. L. Doshchitsin; A. V. Chapurnykh (Рациональная фармакотерапия в кардиологии, 2018)
Aim. Comparison of different treatment tactics – medicated antiarrhythmic therapy (AAT) and radiofrequency ablation (RFA) of elderly and senile pa- tients with relapsing atrial fibrillation (AF) as more severe patients with a burdened comorbid background.Material  and  methods. The study  included  108 patients  with  paroxysmal  and  persistent  AF who  were  in  hospital  and  then  under  outpatient observation for 2 years. Depending on the method of treatment, patients were divided into 2 groups: the group receiving medicated AAT (n=45) and the group  treated with RFA (63 patients). Most patients of the 2nd  group  (n=60) after  the RFA received AAT, i.e. so-called hybrid therapy. These groups  were comparable in age (mean age 64.9 and 64.7 years, respectively), sex and underlying pathology, comorbid diseases.Results. In patients who received "hybrid" therapy after 2 years of observation, it was more often possible to preserve  the sinus rhythm and achieve a reduction in arrhythmia episodes in comparison with the  drug  group  (95.2% and  86.6%, respectively). Quality of life and  the  frequency of complications of AAT in these groups  of patients were comparable.Conclusion: In elderly and senile patients with paroxysmal and persistent atrial fibrillation, RFA and hybrid therapy was more effective for maintaining sinus rhythm compared to drug therapy. After RFA in this category of patients, in most cases, medicated AAT was used. When choosing the tactics of rational AAT in elderly patients, preference should be given to tactics in which it is possible to achieve an improvement in the quality of life.